Pengaruh Brand Image dan Product Quality terhadap Customer Loyalty melalui Customer Satisfaction Sepatu Nike di Kota Bandung - Dea Nurcahyani; Leni Evangalista Marliani (Journal of Management and Bussines (JOMB), 2024)
This research aims to analyze the influence of brand image and product quality on customer loyalty which is mediated by customer satisfaction of Nike shoes in the city of Bandung. The research method uses a quantitative approach with surveys and Likert questionnaires. The research instrument has gone through the validity, reliability, classical, multiple regression and Sobel test stages. SPSS version 25 software tools and an online Sobel calculator were used to analyze the data. The research results show that the second, fourth, fifth and seventh hypotheses successfully reject H0 and the first, third and sixth hypotheses fail to reject H0, which means that brand image has no positive effect on loyalty mediated by customer satisfaction and product quality has a positive effect on customer loyalty mediated by customer satisfaction. In conclusion, product quality has an indirect influence on customer loyalty, mediated by customer satisfaction. Keywords: Brand Image, Product Quality, Customer Loyalty, Customer Satisfaction